2009
DOI: 10.1186/1471-2202-10-s1-o21
|View full text |Cite
|
Sign up to set email alerts
|

Control of the temporal interplay between excitation and inhibition by the statistics of visual input

Abstract: IntroductionIn the primary visual cortex (V1), single cell responses to simple visual stimuli (drifting gratings) are usually strong but with a high trial-by-trial variability. In contrast, when exposed to full field natural scenes with simulated eye movements, the firing patterns of these neurons are sparse but highly reproducible over trials [1]. So far the mechanisms behind these two distinct different response behaviours are not yet fully understood. Different mechanisms are candidates for controlling spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In particular, our study suggests that the brain takes advantages of a simple architecture to filter, process and propagate synchronous events in complex networks. By investigating how these properties are important in a more functional context, such as processing in the visual system (Kremkow et al 2008b), future work will be able to address the functional impact of such architecture onto the dynamics of information processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, our study suggests that the brain takes advantages of a simple architecture to filter, process and propagate synchronous events in complex networks. By investigating how these properties are important in a more functional context, such as processing in the visual system (Kremkow et al 2008b), future work will be able to address the functional impact of such architecture onto the dynamics of information processing.…”
Section: Resultsmentioning
confidence: 99%
“…In the visual system, balancing feedforward inhibition was proposed as a candidate mechanism to explain the invariant orientation tuning observed with drifting gratings (Troyer et al 1998). Interestingly, it was shown in vivo (Marre et al 2005;Haider et al 2010) and in a model of the early visual system (Kremkow et al 2008b) that conductances are indeed correlated during natural viewing. In the model, the correlation of the conductances was related to the correlation of the contrast polarity in the receptive fields of cortical layer 4 neurons.…”
Section: Discussionmentioning
confidence: 94%
“…Teinonen et al (2009) examined statistical learning in sleeping newborns by presenting a continuous stream of three-syllable words in an artificial language similar to that employed by Saffran et al (1996a), in which the only cues to word boundaries were the conditional relations or frequencies of co-occurrence between syllables. Using electroencephalography, they measured newborns’ event-related potential (ERP) negativities to the first, second, and third syllables in the words.…”
Section: Auditory Statistical Learningmentioning
confidence: 99%
“…Even before they begin speaking, however, research has shown that infants can pick up on important and complex linguistic cues from their auditory input, including rhythmical cues (Mehler et al, 1988), phonemic contrasts (e.g., Werker and Tees, 1984; Kuhl et al, 2006), structural regularities (e.g., Christophe et al, 1994), and transitional probabilities (e.g., Saffran et al, 1996; Teinonen et al, 2009; for a review of early infant language development, see Gervain and Mehler, 2010). …”
Section: Introductionmentioning
confidence: 99%